Қарақалпақ эпосларының сырт еллерде үйренилиўиниң тийкарғы илимий аспектлери анализи (SCIENCE and SOCIETY, 2022)
The article provides a detailed analysis of the main scientific aspects of the Karakalpak epics studied by foreign schol- ars on the example of the epic "Edige". Also, the role of these comparative-typological studies in the history of study of Karakalpak epics abroad will be determined on the basis of reliable scientific and theoretical facts.